Empiric dimension of educational quality at preschool - Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of this publication is to actualize the empirical experience of child upbringing problem solving within the context of teaching quality improvement in the preschool. Growing parent trust in preschool teachers raises family demands in the relation to child care and preschool education issues. Therefore, it is becoming more important to improve the indicators of teaching quality, focusing on work progress of the preschool educational institution. Quality of child education to a great extent is the key to child’s individual development and success.